The H2020 OCRE Project Opens the Gates of the Commercial Cloud and EO Services Usage to the Research Community - José Manuel Delgado Blasco; Antonio Romeo; David Heyns; Joao Fernandes; Rob Carrillo; Natassa Antoniou; Lefteris Mamais; Marc-Elian Begin (Emerging Science Journal, 2020)
Cloud and Earth Observation (EO) based services offer the European Research community a wealth of powerful tools. However, for many researchers these tools are currently out of reach. It is difficult to find and select suitable services. Establishing agreements with cloud and EO service providers and ensuring legal and technical compliance requires specialist skills and takes an inordinate amount of time. Equally, service providers find it difficult to reach and meet the needs of the research community in technical, financial and legal areas. The Open Clouds for Research Environments consortium (OCRE) will change this, by putting in place an easy adoption route. In the autumn of 2019, OCRE will run a pan-European tender and establish framework agreements with service providers who meet the requirements of the research community. 10.000 European research and education institutes will be able to directly consume these offerings via the European Open Science Cloud service catalogue, through ready-to-use agreements. They will not have to run a tender of their own. In addition, to stimulate usage, OCRE will make available 9.5 million euro in service credits (vouchers), through adoption funds from the European Commission. OCRE is a pioneer project without precedence, with potentially high impact in the future EO market activities and evolution of service offering, with the objective to burst the usage of EO commercial services by the research environment.